PENGARUH KEGIATAN EKSTRAKURIKULER PRAMUKA TERHADAP PEMBENTUKAN KARAKTER DISIPLIN SISWA SD NEGERI 163 PEKANBARU - Wahyu Nadia Putri; Hendri Marhadi; Zariul Antosa (STKIP Subang, 2026)
This study was motivated by the importance of developing disciplinary character among elementary school students and the need to optimize Scout extracurricular activities as a medium for character education. The purpose of this study was to determine the effect of Scout extracurricular activities on the disciplinary character of students at SD Negeri 163 Pekanbaru. This study employed a quantitative approach with a causal associative research design. The research sample consisted of 25 third-grade students who actively participated in Scout extracurricular activities. Data were collected through questionnaires and closed observations. The questionnaire was administered before and after students participated in Scout activities, while observations were conducted to monitor the development of students’ disciplinary behavior during classroom learning and Scout activities. Data were analyzed using descriptive statistics and simple linear regression with the assistance of SPSS version 27. The results showed that Scout extracurricular activities had a significant effect on students’ disciplinary character. The regression analysis indicated a significance value of 0.001, which was lower than 0.05, confirming that the research hypothesis was accepted. In addition, observational findings revealed improvements in students’ obedience to rules, time discipline, responsibility, cooperation, activeness, and neatness. These findings indicate that regular and structured Scout activities contribute positively to the development of disciplinary character among elementary school students. Therefore, Scout extracurricular activities can serve as an effective strategy for strengthening character education in schools.